Do the characteristics of sharia supervisory board affect the disclosure of Islamic social reporting? - Ratna Sari, Wulan; Pratama, Bima Cinintya; Fakhruddin, Iwan; Wibowo, Hardiyanto (IAIN Surakarta, 2023)
The realm of Islamic accounting research places significant importance on Islamic Social Reporting (ISR), recognizing its indispensable role and considerable impact. The objective of this study is to assess the extent of disclosure in ISR by examining the impact of various factors such as the frequency of Sharia Supervisory Board (SSB) meetings, the presence of multiple positions held by the SSB members, the educational background of the SSB members, and the Islamicity Performance Index (IPI). This study uses a sample of Islamic banks in Indonesia with selected through purposive sampling method and obtained 154 samples that met the criteria. To test the research hypothesis, panel data regression model analysis was used. The results show that the frequency of SSB Meetings and Zakat Performance Ratio (ZPR) has a positive impact on the disclosure of ISR. The concurrent position of the SSB has no effect on the disclosure of ISR. The educational background of the SSB has no effect on the disclosure of ISR. Several other variables in the IPI also do not affect the disclosure of ISR because high and low financing, income distribution, comparison of director and employee salaries, and income and investment channels are considered not to affect the disclosure of ISR. The findings of this study offer valuable insights suggesting that augmenting the frequency of meetings conducted by the SSB and increasing zakat contributions made by Islamic commercial banks in Indonesia can result in an improved level of disclosure pertaining to ISR by the respective companies.